Editorial for the special issue: "Novel solutions and novel approaches in operational research" - Samo Drobne; Lidija Zadnik Stirn; Berislav Žmuk (Business Systems Research (BSR), 2022)
This special issue of Business Systems Research (SI of the BSR) is being co-published by the Slovenian Society INFORMATIKA - Section for Operational Research (SSI -SOR). It focuses on recent advances in Operations Research and Management Science (OR / MS), with a particular emphasis on linking OR / MS with other areas of quantitative and qualitative methods in the context of a multidisciplinary framework. The ten papers that were chosen for this Special Issue of the BSR present advancements and new techniques (methodology) in the field of Operations Research (OR), as well as their application in a variety of fields, including risk management, mathematical programming, game theory, gravity, spatial analysis, logistics, circular economy, continuous improvement, sustainability, e-commerce, forecasting, Gaussian processes, linear regression, multi-layer perceptron, and machine learning.
Keywords: 330; interdisciplinary research; operations research; risk management; mathematical programming; game theory; gravity; spatial analysis; logistics; circular economy; continuous improvement; sustainability; e-commerce; forecasting; Gaussian processes; linear regression; multi-layer perceptron; machine learning